2012
DOI: 10.1021/bi300698h
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structures of Magnesium and Manganese Complexes with the N-Terminal Domain of Calmodulin: Insights into the Mechanism and Specificity of Metal Ion Binding to an EF-Hand

Abstract: Calmodulin (CaM), a member of the EF-hand superfamily, regulates many aspects of the cell function by responding specifically to micromolar concentrations of Ca2+ in the presence of ~1000× higher concentration of cellular Mg2+. To explain the structural basis of metal ion binding specificity we have solved the X-ray structures of the N-terminal domain of calmodulin (N-CaM) in complexes with Mg2+, Mn2+ and Zn2+. In contrast to Ca2+, which induces domain opening in CaM, octahedrally coordinated Mg2+ and Mn2+ sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
58
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 69 publications
6
58
1
Order By: Relevance
“…The residues involved in Mg 2+ ligation and their corresponding chemical shift values were similar to those reported for free N‐terminal CaM 22. It has been shown that the smaller ionic radius of the Mg 2+ ion has different coordination geometry than the larger Ca 2+ , which limits the conformation plasticity in EF‐hand proteins 12, 22. Additionally, we found that residues mapping to sites I and II were perturbed in a way that is indicative of Mg 2+ ion coordination at each metal‐binding loop.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…The residues involved in Mg 2+ ligation and their corresponding chemical shift values were similar to those reported for free N‐terminal CaM 22. It has been shown that the smaller ionic radius of the Mg 2+ ion has different coordination geometry than the larger Ca 2+ , which limits the conformation plasticity in EF‐hand proteins 12, 22. Additionally, we found that residues mapping to sites I and II were perturbed in a way that is indicative of Mg 2+ ion coordination at each metal‐binding loop.…”
Section: Resultssupporting
confidence: 71%
“…This is in direct contrast to TnC, which has monodentate ligation of the Mg 2+ ion mediated through Oε1 of Glu in the presence of target peptide 11, 30. TnC has been demonstrated to undergo a compaction in of the metal‐binding loops in the Mg 2+ ‐loaded state 11, whereas CaM does not coordinate Mg 2+ through the −Z ligand, so metal ligation is limited to the N‐terminal portion of the loop 12, 22. Metal binding specificity can be controlled by the amino acid side‐chain present at position 12 of the EF‐hand loop.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations